Isolasi Mikroba Endofit Dari Kulit Batang, Daun, dan Kulit Buah Manggis (Garcinia mangostana L.) Pengkulturan Serta Uji Aktivitas Antimikrobanya - Akmal Djamaan; Asia Asia; Rina Wahyuni (Jurnal Farmasi Higea, 2014)
The antimicrobial activity of endophytes microbe that symbiosis with mangosteen had been carried out. There were 12 fungal’s  isolates and 14 bacterial’s isolates had been isolated from cortex, lief, and pericarp of Garcinia mangostana L. Each fungal’s isolates were fermented in Soybean Extract Broth liquid medium for 1 week at on a rotary shaker incubator at a 25-270 C and 90 rpm speed. Each bacterial’s isolates were fermented in water corn soaked medium for 24 hours on a rotary shaker incubator at 300C and 120 rpm speed. Fermented fungal’s and bacterial’s were tested their antimicrobial’s activity against Staphylococcus aureus, Escherichia coli and Candida albicans with agar diffusion methode. The result showed that J-G1 (Candida sp) and J-T1 (Candida sp) were fungal’s isolates that ware active against Escherichia coli with inhibition diameter 10 mm. J-H1 (Curvularis sp), J-G2 (Candida sp), J-T1 (Candida sp) were fungal’s isolates that were active against Staphylococcus aureus with inhibition diameter 9 mm, 11 mm and 13 mm respectively. B-T2 (Klebsiella sp)and B-K51 (Bacillus sp1) were bacterial’s isolates that were active againts Escherichia coli with inhibition diameter 13 mm and 18 mm respectively. B-H (Bacillus sp2), B-G (Bacillus sp2), B-P1 (Bacillus sp1), B-K101(Bacillus sp1) and B-K102 (Bacillus sp1) were bacterial’s isolates that were active againts Staphylococcus aureus with inhibition diameter 11 mm, 14 mm, 15 mm, 16 mm and 15 mm respectively.